Identification and preclinical efficacy evaluation of two lytic bacteriophages targeting highly virulent and multidrug-resistant Klebsiella pneumoniae - Ai Guo; Dianbao Zuo; Li Shi; Ming Guo; Jinquan Li; Caili Li; Puqing Wang; Xiaodong Sun; Ming Sang (Annals of Clinical Microbiology and Antimicrobials)
Abstract Background The emergence of MDR K. pneumoniae poses a critical challenge in treating respiratory-associated pneumonia. Bacteriophages are promising antibiotic alternatives with unique features. This study aimed to isolate new bacteriophages from the hospital environment and investigate their therapeutic potential and mechanisms. Methods We employed plaque assays, transmission electron microscopy, and whole-genome sequencing to systematically characterize the biological properties, morphology, and genomic profiles of the phages in parallel. The bacteriostatic curve, biofilm staining quantification, and biofilm inhibition rate assay were employed to evaluate the in vitro lytic efficacy of the phage. More importantly, we established the murine pneumonia infection models through nasal instillation, assessed the therapeutic potential of the phage in vivo by observing pathological morphology via HE staining, detecting pro-inflammatory cytokine levels via qPCR and ELISA, and monitoring bacterial load changes in lung tissue through PCR analysis. Results Phages vB_KpnP_XY3 and vB_KpnP_XY4, taxonomically classified as Siphoviridae, demonstrated broad temperature (4–60 °C), pH (4–11) tolerance, chloroform resistance, latent periods of 40/35 min, and burst sizes of 340/126 PFU/cell. Both genomes contained circular dsDNA genomes (47,466 bp/50,036 bp) without virulence or antibiotic resistance genes. The bacterial concentration markedly decreased at 2 h post-treatment, reaching its biological nadir by 6 h. Concurrent biofilm assays demonstrated 80% biofilm inhibition and rapid bacterial clearance. In murine pneumonia models, both phage monotherapy and phage-antibiotic combinations significantly reduced bacterial loads compared with antibiotics alone (P < 0.05), concurrently attenuating inflammation (IL-1β/IL-6/TNF-a. P < 0.0001) and restoring alveolar architecture with reduced necrosis. Conclusion The phages vB_KpnP_XY3 and vB_KpnP_XY4 demonstrated robust environmental adaptability. Its antibacterial effect is related to its specific biofilm dissolution performance in vivo and in vitro. These findings provide strong evidence for the precise phage treatment of MDR K. pneumoniae infections.